Dye-tracer-aided investigation of xylem water transport velocity distributions - S. Seeger; S. Seeger; M. Weiler (Hydrology and Earth System Sciences, 2023)
The vast majority of studies investigating the source depths in the soil of root water uptake with the help of stable water isotopes implicitly assumes that the isotopic signatures of root water uptake and xylem water are identical. In this study we show that this basic assumption is not necessarily valid, since water transport within a plant's xylem is not instantaneous. However, to our knowledge, no study has yet tried to explicitly assess the distribution of water transport velocities within the xylem. With a dye tracer experiment, we were able to visualize how the transport of water through the xylem happens at a wide range of velocities which are distributed unequally throughout the xylem. In an additional virtual experiment we could show that, due to the unequal distribution of transport velocities throughout the xylem, different sampling approaches of stable water isotopes might effectively lead to xylem water samples with different underlying age distributions.